Media Law, Ethics, and Policy in the Digital Age - Mhiripiri, Nhamo A.; Chari, Tendai (IGI Global, 2021)
The growing presence of digital technologies has caused significant changes in the protection of digital rights. With the ubiquity of these modern technologies, there is an increasing need for advanced media and rights protection.